The Clouded Crystal Ball - Heilbroner, Robert L. (American Economic Review, 1974)
I shall begin this brief discussion of the policy issues of the 1970's by taking a look backward, rather than forward, reviewing some of the major issues of the I should have raised were I speaking in the early 1950's instead of the early 1970's. With perfect foresight, I would, of course, have mentioned the issue of economic growth, clearly visible as the central thrust of all the advanced industrial societies; the recalcitrant problem of inflation; the constraint of the environment as a wholly new and important element for both micro and macro policy; the difficulties implicit in Japan's remarkable reentry into the world economy; the emergence of the multinational corporation as a new agency for the conduct of international economic relationships; the problem of economic development, stubbornly resisting attempts to move traditional societies off dead center by the application of standard economic nostrums; and the problem of the dollar and what to do about it. Three aspects are common to all these future problems of the past. First, these are unmistakably economic, rather than political or sociological. Second, they are all deep-seated rather than accidental or superficial economic problems. Last, and most important, every one of these problems was invisible in the 1950's. In point of fact, had I really been holding forth on the outlook in the early 1950's, I doubt that I would have mentioned a single one of them. For in those earlier years, it was not growth but the threat of chronic recession that still absorbed the attention of the profession. Inflation was a matter on which no sessions were organized, because we knew that it could not occur as long as unemployment was 4 or 5 percent of the labor force. The Sierra Club may have been exercised over the deterioration of the environment, but not the American Economic Association. No one had heard of the multinational corporation. Japan was considered by all to be a hopeless economic invalid. The prevailing attitude toward economic growth in the less-developed countries was one of encouragement, not to say enthusiasm: I believe the 1950's were officially dubbed the Decade of Development. The problem of the dollar, you will remember, was that it was deemed to be in more or less permanent short supply. Now I do not mention this extraordinary myopia to take the profession to task. I raise it, rather, to inject a cautionary note in making our projections and predictions today. Like everyone else, I have my list of expected policy issues of the 1970's-a surprise-free list, in Herman Kahn's terminology. It includes the very problems I have just enumerated: growth, inflation, the environment, the multinationals, the failure of development, the international monetary situation. But I am moved to ask, reflecting on the past, whether this list of problems is likely to be as miscon* Norman Thomas Professor, New School for Social Research.